Inclination and inter-row spacing optimization for 12MW floating photovoltaic system with shading loss and financial analysis - T. Paphapote; W. Bamrungsawat; T. Wongwuttanasatian (Results in Engineering, 2025)
Global photovoltaics energy generation is expected to grow at 600 TWh annually over the next three years. With lower cost of photovoltaics panels, policymakers worldwide are increasingly supporting the construction of photovoltaics plants. In Thailand, the government encourages the use of renewable energy by providing 24 % of the support toward floating photovoltaics. This research evaluates and optimizes the inclination and inter-row spacing of floating photovoltaics in Maptaphut Industrial Estate, Rayong Province, Thailand. PVsyst program is utilized to simulate energy production at the proposed location with various inclination angles and inter-row spacings. Net Present Value, Internal Rate of Return, Benefit to Cost ratio, and Payback Period are used to assess the project’s financial feasibility. Due to the nature of simulation, sensitivity analysis is performed by varying electricity price and investment cost. Results show an increasing concave down relationship between energy production and inter-row spacing. The highest energy production does not offer the best financial outcome. Financial and shading analysis suggests an optimized configuration at 6° South and 1.00 m inter-row spacing. The project remains financially feasible under sensitivity analysis, considering power generation, shading loss, and financial outcomes, subject to 5.9 % uncertainty from simulation weather data.